Organization of virtual interaction in the context of the coronavirus pandemic - Voronova, Elena M. (2020)
The organization of the educational process should be carried out taking into account the epidemiological situation and following the requirements that are due to quarantine measures. The leadership of vocational schools is looking for ways to conduct classes in a safe environment, assessing the potential risks for teachers and students. Higher schools implement the possibilities of electronic technologies as a factor in ensuring the safety of subjects of the educational process for communication between students and teachers at a distance. The purpose of the article is to review the experience of organizing virtual interaction between students and teachers within the framework of e-learning during the spread of coronavirus infection. The article reveals the possibilities of electronic technologies that allow communicating at a remote distance. The preparation of students in critical conditions is carried out using various electronic means that promote active interaction. The results of the study reflect the opinion of students of higher educational institutions about the use of virtual interaction tools. The results obtained using the Likert scale allow us to say that the majority of the respondents are active participants in virtual interaction and are ready to continue to communicate using the presented means despite the existing difficulties.